(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article provides a scientific analysis of priority approaches until improving the efficiency of investment activities in industrial enterprises . Using updated statistical data for 2025, it conducts a comparative and structural assessment of Uzbekistan’s fixed capital investment volumes, industrial output growth rates, and the dynamics of foreign investment. The study systematizes the key determinants of investment efficiency and substantiates their linkage to economic performance through technological modernization, the acceleration of innovation activity, the improvement of financial management mechanisms, and the enhancement of the investment climate’s attractiveness. The findings offer a methodological basis for developing applied recommendations to support investment project selection, resource allocation, and the optimization of investment decision-making in industrial enterprises.